Self-Assessment of Individual Differences in Language Switching - Rodriguez-Fornells, Antoni; Kramer, Ulrike; Lorenzo-Seva, Urbano; Festman, Julia; Münte, Thomas F. (Frontiers in Psychology, 2012)
Language switching is omnipresent in bilingual persons. In fact, the ability to switch languages (code switching) is a very fast, efficient and flexible process which seems to be a fundamental aspect of bilingual language processing. Here we aimed to characterize individual differences in language switching psychometrically and to create a reliable measure of this behavioral pattern by introducing a Bilingual Switching Questionnaire (BSWQ). As a working hypothesis and based on the previous literature on code switching we decomposed language switching into four constructs: (i) L1 switching tendencies (the tendency to switch to L1) (L1-switch), (ii) L2 switching tendencies (L2-switch); (iii) Contextual Switch (CS), which indexes the frequency of switches usually triggered by a particular situation, topic or environment and, (iv) Unintended Switch (US), which is measuring the lack of intention and awareness of the language switches. A total of 582 Spanish-Catalan bilingual university students was studied. Twelve items were selected (three for each construct). The correlation matrix was factor-analyzed using Minimum Rank Factor Analysis (MRFA) followed by oblique Direct Oblimin rotation. The overall proportion of common variance explained by the four extracted factors was .86. Finally, in order to assess the external validity of the individual differences scored with the new questionnaire, we evaluated the correlations between these measures and several psychometric (language proficiency) and behavioral measures related to cognitive and attentional control. The present study highlights the importance of assessing individual differences in language switching when studying the interface between cognitive control and bilingualism.